“A Coal-Black Flower of Hell!”: The Influence of Robert Southey’s “The Origin of the Rose” on Robert Browning’s “The Heretic’s Tragedy” - Baker, John (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
Robert Browning first published “The Heretic’s Tragedy” in his best-known collection of poems, Men and Women, in 1855. The poem is supposedly a medieval theatrical performance, or “interlude,” depicting the execution by burning of the accused heretic Jacques de Molay, Grand Master of the Knights Templar, in Paris in 1314. It is a weird and disturbing work, which has hitherto received little critical attention. It is the contention of this article that a major and previously unidentified source for this work is Robert Southey’s 1798 poem “The Origin of the Rose,” which is based on a Christian legend initially recounted in Sir John Mandeville’s medieval travel narrative The Book of Marvels and Treasures. The legend tells of a Jewish woman from Bethlehem unjustly accused of fornication, who is saved from burning through divine intervention. Browning’s poem deliberately “reverses” Southey’s in situation, outcome, and imagery (specifically, the depiction of roses). This article discusses “The Heretic’s Tragedy” in relation to Browning’s critical depiction of Roman Catholicism in his work at this period, as well as the poet’s knowledge of Southey’s work and career.